Implementation of SOLO taxonomy and Newman error analysis in first-order differential equation - Yarman, Yarman; Murni, Dewi; Tasman, Fridgo (Jurnal Infinity, 2025)
First-order Ordinary Differential Equation (ODE) has many applications in physics, engineering, biology, economics, and ecology. Therefore, mastering the concepts and methods of solving ODE is essential for students to be able to apply mathematics in solving real-world problems. However, the teaching of first-order ODE has not paid attention to practical applications, so that students have difficulty linking theory with real cases. This study aims to analyze the implementation of the SOLO taxonomy and Newman Error Analysis (NEA) in first-order ODE. The methodology used is a case study. The research subjects consisted of nine students of the mathematics department of FMIPA Universitas Negeri Padang. Data were collected through tests, interviews, and documentation. Then the data were analysed quantitatively and qualitatively. The results showed that there were five errors in solving first-order ODE made by students, namely Reading Errors (RE), Comprehension Errors (CE), Transformation Errors (TE), Process Skill Errors (PE), and Encoding Errors (EE). Some of the causes of these errors include students' low ability to read mathematical symbols, students' inaccuracy, not being able to use algorithms correctly, not mastering the concepts of algebra, differential, and integral, as well as not understanding in determining the systematic solution of the problem and not being accustomed to writing the final answer. This information can be used as a guideline for lecturers in designing strategies and lecture designs for first-order ODE.